Knowledge on Down Syndrome and Down Syndrome prenatal screening tests among pregnant women in Kuantan, Pahang - Abdul Ghafar, Nurul Fatehah; Muhammad, Siti Aeshah @ Naznin; A. Talib, Norlelawati; Roslani, Anna Liza; Ismail, Rozihan; Zainuddin, Norafiza (2019)
Down syndrome is the most common trisomy disorders among live births, with advanced maternal age being an established risk factor. Prenatal screening for this condition includes non-invasive prenatal testing such as assessment of nuchal translucency thickness by ultrasonography and measurement of biochemical markers in maternal serum during the first trimester of pregnancy. The subsequent diagnostic invasive procedures such as chorionic villus sampling is aimed at determining the foetal karyotype. The objective of this study is to assess the knowledge of Down syndrome and its screening test among pregnant women in Kuantan, Pahang. This cross-sectional study was conducted from August 2018 to February 2019 involving five Maternal and Children Health facilities in Kuantan, Pahang using self-administered validated questionnaires. The data was analysed using SPSS version 22. There were a total of 189 respondents with the age ranging from 18-45 years (30.34 ± 0.38). The mean pregnancy weeks was 29.61 ± 9.11. Approximately 53% of the respondents were able to answer correctly more than half of the questions posed (> 5 of 9) regarding the knowledge of Down Syndrome (mean score 5.6 ± 1.8). As for the knowledge on the prenatal screening, about 48% could answer correctly more than half of the questions posed (≥6 of 12) with a mean score of 5.5± 3.2. The level of knowledge of Down syndrome was found to be significantly associated with maternal education level (p<0.001) while maternal age was significantly associated with the level of knowledge of Down syndrome prenatal screening (p=0.004). The results show that the pregnant women in this study did not have adequate level of knowledge on Down syndrome and its prenatal screening tests. Intervention programmes at the health facilities could be carried out to increase the knowledge.